2012
DOI: 10.1038/gim.2012.13
|View full text |Cite
|
Sign up to set email alerts
|

International normative perspectives on the return of individual research results and incidental findings in genomic biobanks

Abstract: Managers of genomic biobanks constantly face ethical and legal challenges ranging from issues associated with the informed consent process to procedural concerns related to access by researchers. Yet, with the availability of next-generation sequencing technologies, one topic is emerging as the focus of ongoing debate: the return of individual research results and incidental findings to participants. This article examines this topic from an international perspective, where policies and guidelines discussing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 17 publications
1
40
0
1
Order By: Relevance
“…Zawati and Knoppers (2012) have suggested that international norms ought to be set up to guide the return of individual research results and incidental fi ndings based on biobank research as one way of ameliorating some of these problems arising from this misconception. We argue, however, that attempts to set up international norms and guidelines fail to address the fundamental change that is going on in medical research.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Zawati and Knoppers (2012) have suggested that international norms ought to be set up to guide the return of individual research results and incidental fi ndings based on biobank research as one way of ameliorating some of these problems arising from this misconception. We argue, however, that attempts to set up international norms and guidelines fail to address the fundamental change that is going on in medical research.…”
Section: Discussionmentioning
confidence: 99%
“…A number of recent studies have identifi ed inconsistencies between international norms and guidelines on the return of IRR and IF, and the practices associated with biobanking. The studies note that there is no international consensus on the ways in which information from biobanking research should be returned to individuals (Wolf, 2013;Zawati & Knoppers, 2012;Bledsoe et al, 2013;Forsberg et al, 2009). Many of these studies have called for international guidelines regarding the return of IRR and IF (Zawati & Knoppers, 2012).…”
Section: Biobanks and Ambivalent Research Settingsmentioning
confidence: 99%
See 3 more Smart Citations